2014
DOI: 10.1063/1.4892596
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation species on surface-induced phase transition observed for platinum complex anions in platinum electrodeposition using nanoporous silicon

Abstract: In an earlier work [K. Fukami et al., J. Chem. Phys. 138, 094702 (2013)], we reported a transition phenomenon observed for platinum complex anions in our platinum electrodeposition experiment using nanoporous silicon. The pore wall surface of the silicon electrode was made hydrophobic by covering it with organic molecules. The anions are only weakly hydrated due to their large size and excluded from the bulk aqueous solution to the hydrophobic surface. When the anion concentration in the bulk was gradually inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…On the other hand, the SIFT that occurs during metal electrodeposition within nanoporous electrode does explain the deposition behavior in the nanopores. 21,22 The enrichment of reactants resulting from SIFT is known to promote dense metal deposition within porous silicon electrodes, because large metal ions that are weakly hydrated also behave as rather hydrophobic solutes. 21,22 Although the zerovalent zinc complexes are predicted to be slightly polarized, these complexes exhibit weaker hydration properties than the ionic species.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the SIFT that occurs during metal electrodeposition within nanoporous electrode does explain the deposition behavior in the nanopores. 21,22 The enrichment of reactants resulting from SIFT is known to promote dense metal deposition within porous silicon electrodes, because large metal ions that are weakly hydrated also behave as rather hydrophobic solutes. 21,22 Although the zerovalent zinc complexes are predicted to be slightly polarized, these complexes exhibit weaker hydration properties than the ionic species.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The deposition rate required for metallic zinc considered in the present study is much higher than that actually occurring for platinum mentioned above. Theoretically, under the conditions of SIFT, fast supply of zinc precursors into the nanopores can be realized and the depletion does not occur even when they are rapidly consumed within the nanopores due to high-rate charging.…”
Section: Introductionmentioning
confidence: 99%
“…At the single-digit nanometer scale, recent research has revealed that the conventional strategy employing hydrophilic treatment is no longer the optimum method. Because interactions with the solvent (water molecules in an aqueous solution) in deposition baths are not negligible at the nanometer scale, some studies, including our previous report, have shown that the solvation properties (hydrophobicity in an aqueous solution, solvophobicity in nonaqueous solution, and ionophobicity in an ionic liquid) of the solute and surface play significant roles in enhancing electrochemical properties such as in electrodeposition and electric double layer capacitors. …”
Section: Introductionmentioning
confidence: 95%
“…10,13,14 Theoretical analysis based on integral equation theory for molecular liquids, a statistical−mechanical theory, suggested that the number density of metal complexes can be orders of magnitude higher with the occurrence of the SIFT in nanopores. 8,9 There exists a strong relationship between the occurrence of SIFT in nanopores and the local enhancement of electrodeposition. However, we have not obtained clear and direct evidence of the accumulation by SIFT.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When using a porous electrode, homogeneous distribution of metal nanoparticles along the porous layer is normally difficult to achieve. Recently, we succeeded in generating a uniform deposition of Pt within a nanoporous silicon layer by tuning the hydration properties of porous electrodes as well as Pt complex anions [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%